Пошаговое объяснение:
0,7(6у-5)=0,4(у-3)-1,16
4,2y - 3,5 = 0,4y - 1,2 - 1,16
4,2y - 3,5 = 0,4y - 2,36
4,2y - 0,4y = 3,5 - 2,36
3,8y = 1,14
y = 1,14 : 3,8
y = 0,3
4,2y-3,5=0,4y-1,2-1,16
4,2y-3,5=0,4y-2,36
4,2y-0,4y=-2,36+3,5
3,8y=1,14
y=0,3
Пошаговое объяснение:
0,7(6у-5)=0,4(у-3)-1,16
4,2y - 3,5 = 0,4y - 1,2 - 1,16
4,2y - 3,5 = 0,4y - 2,36
4,2y - 0,4y = 3,5 - 2,36
3,8y = 1,14
y = 1,14 : 3,8
y = 0,3
0,7(6у-5)=0,4(у-3)-1,16
4,2y-3,5=0,4y-1,2-1,16
4,2y-3,5=0,4y-2,36
4,2y-0,4y=-2,36+3,5
3,8y=1,14
y=0,3